Application of ZigBee for pollution monitoring caused by automobile exhaust Gases - Eren, Halit; Al-Ghamdi, A.; Luo, J. (2009)
Gases emitted from automobile exhausts have been monitored using a gas sensor arrays. The information from the sensor array has been transmitted to a remote location by ZigBee wireless technology. Quantitative and qualitative analysis of gases has been conducted at the remote location by a computer. Programs have been developed in LabView and excel to display data and alarm conditions. Results indicate that unlike the automobiles using natural gas the unleaded and premium unleaded fuel automobiles can have significant effect on the environment conditions due to their high level of toxic gas emission. © 2009 IEEE.